Pelaksanaan Pengawasan terhadap Kode Etik dan Perilaku Hakim Konstitusi di Indonesia - Khusnul Catur Prasetya; Moh Sa’diyin (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2024)
The role of constitutional judges to uphold the justice is very important and strategic, for that reason all of requires the judges is a statesman, should also have good attitudes and behavior. Thus every constitutional judges need to do the monitoring of they behavior in order to protect the good name of the judicial institution. All of the judges, like Supreme Court justices or constitution judges are necessarily equate to an equivalent position, so it must be placed within the framework of democracy. The consequences is throught the third amendment of UUD 1945, the external controling for all of the judges implemented by creating the judicial commission. However, a growing mind at that moment only lead to Supreme Court justice and ranks, when it should be also the constitution judges within the framework of democratic and the judicial commission controled. Especially in socio-political, the formation of the judicial commission is in intended to strengthen the corruption eradication agenda, especially what happened in the sphere of justice within role of judge in integrity and well behaved, to ensure that the judicial function is implemented in independent, fair, clean and transparent